2012
DOI: 10.1136/archdischild-2011-300578
|View full text |Cite
|
Sign up to set email alerts
|

C reactive protein: impact on peripheral tissue oxygenation and perfusion in neonates

Abstract: Inflammatory processes with CRP elevation cause impaired peripheral oxygenation and perfusion in neonates even when routine haemodynamic variables are still normal. NIRS might offer a new non-invasive tool for the early recognition and diagnosis of infectious and non-infectious inflammatory processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
0
25
1
2
Order By: Relevance
“…They found lower values of TOI, oxygenated and deoxygenated haemoglobin and blood volume in the affected limb compared to the unaffected one. Nonetheless, the TOI values in the unaffected group were also low compared to other studies [1,3,13,14,15,17,18,19,27]. We can only speculate on this observation.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…They found lower values of TOI, oxygenated and deoxygenated haemoglobin and blood volume in the affected limb compared to the unaffected one. Nonetheless, the TOI values in the unaffected group were also low compared to other studies [1,3,13,14,15,17,18,19,27]. We can only speculate on this observation.…”
Section: Discussioncontrasting
confidence: 47%
“…All 41 studies performed peripheral muscle NIRS measurements in human neonates. Twenty-one studies were identified to use peripheral muscle NIRS measurements as a single method [1,3,6,7,8,9,10,11,12,13,14,15,16,17,18,19,23,24,25,27,28] (table 1), 17 studies combined cerebral and peripheral muscle NIRS measurements [20,21,22,29,30,31,32,33,34,35,36,37,38,39,40,41,42] (table 2) and 1 study used multi-site NIRS measurements [43] (table 2) in human neonates. Two randomized studies were identified [12,36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(11)(12)(13) Recently, our study group was able to show differences in peripheral oxygenation and perfusion in neonates with CRP elevation. (14) The aim of this study was to demonstrate a possible association between varying leukocyte counts and peripheral tissue oxygenation/perfusion measured with NIRS in term and preterm neonates. We hypothesized that peripheral oxygenation and perfusion would be impaired in association with increasing leukocyte counts.…”
Section: Introductionmentioning
confidence: 99%